Ancestral Zuni Glaze-Decorated Pottery : Viewing Pueblo IV Regional Organization through Ceramic Production and Exchange - Huntley, Deborah L., 1969- (Book collections on Project MUSE., 2008)
In the Pueblo IV period (1275-1600) potters began to make distinctive polychrome vessels, which have been linked by archaeologists to new ideologies and religious practices in the area. This research examines interaction networks along settlement clusters in the Zuni region of west-central New Mexico in the thirteenth and fourteenth centuries, using analytical techniques such as INAA sourcing of ceramic pastes.